City-level hukou-based labor market discrimination and migrant entrepreneurship in China - Jie Chen; Mingzhi Hu (Technological and Economic Development of Economy, 2021)
A previously undocumented association between city-level degree of hukou-based labor market discrimination and migrant’s individual entrepreneurship engagement is examined. Applying the Oaxaca–Blinder decomposition analysis on the micro data from the China Migrants Dynamic Survey (CMDS) suggests that hukou-based labor market discrimination can on average explain a 6.3% differential in personal income for rural migrants relative to otherwise identical urban migrants. A one standard deviation increase in a city’s average hukou-based labor market discrimination is associated with roughly 2.9 percentage point higher of entrepreneurship rate among rural migrants, holding other things equal. Furthermore, city-level hukou-based labor market discrimination is associated with much higher propensity for engagement in necessitybased entrepreneurship compared with opportunity-based entrepreneurship. Our empirical work also suggests that the association between city-level hukou discrimination and migrant entrepreneurship is more prominent for people with middle level of education, young people, married people, and renters. Policy implications of these findings are discussed.